Antitumour and Thermogravimetric Studies of Transition Metal Complexes of the Schiff Base Anthracene-9-Carboxaldehyde Thiosemicarbazone - Thomas, Joby; Parameswaran, Geetha (Asian Journal of Chemistry, 2010)
The complexes of transition metals with anthracene-9-carboxaldehyde thiosemicarbazone, (A9CTSC) have been prepared and characterized. Square-planar geometry has been assigned to all these complexes, although the Cu(II) chelate exists in a dimeric form. A9CTSC acts as a monovalent bidentate ligand in all these complexes using the donor sites azomethine nitrogen and thiolate sulphur atoms. The thermal decomposition kinetics and mechanism of these chelates were studied from thermogravimetric data. The kinetic parameters, namely activation energy, E, pre-exponential factor, A, and entropy of activation, ΔS, were calculated from the TG and DTA curves using mechanistic and nonmechanistic integral equations. The ligand and Cu(II) complex were screened for their possible antitumour activity and the chelate was appreciably active in reducing mice tumours. X-ray diffraction pattern of one of the chelate [CdL2] was examined and successfully indexed.